Decreasing the Lag Between Result Availability and Decision-Making in the Emergency Department Using Push Notifications - Christian Koziatek; Jordan Swartz; Eduardo Iturrate; Dina Levy-Lambert; Paul Testa (Western Journal of Emergency Medicine, 2019)
Introduction: Emergency department (ED) patient care often hinges on the result of a diagnostic test. Frequently there is a lag time between a test result becoming available for review and physician decision-making or disposition based on that result. We implemented a system that electronically alerts ED providers when test results are available for review via a smartphone- and smartwatch-push notification. We hypothesized this would reduce the time from result to clinical decision-making. Methods: We retrospectively assessed the impact of the implementation of a push notification system at three EDs on time-to-disposition or time-to-follow-up order in six clinical scenarios of interest: chest radiograph (CXR) to disposition, basic metabolic panel (BMP) to disposition, urinalysis (UA) to disposition, respiratory pathogen panel (RPP) to disposition, hemoglobin (Hb) to blood transfusion order, and abnormal D-dimer to computed tomography pulmonary angiography (CTPA) order. All ED patients during a one-year period of push-notification availability were included in the study. The primary outcome was median time in each scenario from result availability to either disposition order or defined follow-up order. The secondary outcome was the overall usage rate of the opt-in push notification system by providers. Results: During the study period there were 6115 push notifications from 4183 ED encounters (2.7% of all encounters). Of the six clinical scenarios examined in this study, five were associated with a decrease in median time from test result availability to patient disposition or follow-up order when push notifications were employed: CXR to disposition, 80 minutes (interquartile range [IQR] 32–162 minutes) vs 56 minutes (IQR 18–141 minutes), difference 24 minutes (p<0.01); BMP to disposition, 128 minutes (IQR 62–225 minutes) vs 116 minutes (IQR 33–226 minutes), difference 12 minutes (p<0.01); UA to disposition, 105 minutes (IQR 43–200 minutes) vs 55 minutes (IQR 16–144 minutes), difference 50 minutes (p<0.01); RPP to disposition, 80 minutes (IQR 28–181 minutes) vs 37 minutes (IQR 10–116 minutes), difference 43 minutes (p<0.01); and D-dimer to CTPA, 14 minutes (IQR 6–30 minutes) vs 6 minutes (IQR 2.5–17.5 minutes), difference 8 minutes (p<0.01). The sixth scenario, Hb to blood transfusion (difference 19 minutes, p=0.73), did not meet statistical significance. Conclusion: Implementation of a push notification system for test result availability in the ED was associated with a decrease in lag time between test result and physician decision-making in the examined clinical scenarios. Push notifications were used in only a minority of ED patient encounters.